A single session of coordinative motor training does not improve spatial ability performances in healthy children - Morawietz, Christina; Wissmann, Anna Maria; Kuehne, Till; Muehlbauer, Thomas (Frontiers in Sports and Active Living, 2024)
Background In recent years, studies have found small-to-medium positive effects of physical activity on academic achievement. Already acute bouts of exercise appear to improve certain cognitive functions. Spatial abilities are one aspect of cognition that is encountered frequently in daily life and that is closely related to success in science, technology, engineering, and mathematics (STEM)-subjects. However, little is known about the effects of an acute exercise session on spatial abilities. The aim of this study was therefore to evaluate the effect of a single session of coordinative motor training (CMT) on spatial ability performances in healthy children. Methods Forty-nine children were assigned to either a single session of CMT (i.e., obstacle course with motor coordinative and spatial elements) (n = 25, 12 females, mean age: 10.7 ± 0.6 years) or a resting control group (n = 24, 12 females, mean age ± SD: 11.4 ± 0.5 years). Spatial abilities were evaluated in both groups using the Paper Folding Test (PFT), Mental Rotation Test (MRT), Water Level Task (WLT), Corsi Block Test (CBT), and Numbered Cones Run (NCR). Results A statistical main effect for Test was observed for the majority of outcomes (i.e., all but the MRT). Test × Group interactions did not reach the level of significance. Conclusion The results indicate that a single session of CMT does not improve spatial ability performances of healthy children. Future research should evaluate whether repeated longer-term interventions might be more suitable to generate significant improvements in spatial abilities.